Imperialismo e direitos humanos: crítica epistêmica ao fenômeno de representação jurídica - Bandeira, João Adolfo Ribeiro (2014)
Given the importance of human rights as a social technology universally recognized, is discussed in this paper the process of political-legal and philosophical composition of these rights. Supported on epistemic critique and having the marxist current as a theoretical reference, it uses the category of imperialism in order to redefine the applicability of Human Rights. Therefore, utilizes the historical-descriptive method in order to revisit the phenomenon of legal representation. As a method of approach was used the dialectical method because it allows the insertion of own categories to critical analysis of Human Rights, making even possible the contention about the role of the state and the establishment of private property as a fundamental guarantee. Structurally is divided into three sections, each containing two parts. The first emphasizes the constitution of the human being as an individual and social being, and Law as a general and abstract parameter institutional coercive. The second builds the epistemic bases of the instrumentalisation of human rights as a form of imperialist imposition. Finally, in the third chapter, retakes the definitions previously explored having as verification tools the supranational entities consubstantieted in contemporary global society.